A study on the prevalence of the hepatitis B virus among UPCD dental clinicians and practising dentists - Macasaet, Ma. Cristina M.; Singson, Rowena B.; Lingao, Augusto (Adviser).
To determine the prevalence of HBs-Ag among Philippine dental practitioners and clinicians and if there is a direct relationship between the incidence of HBV and the length of time of dental practice, blood was extracted from 213 dental practitioners and 20 UPCD senior dental clinicians and was analyzed for the presence of HBs-Ag and anti-HBs which are used as serologic markers for the Hepatitis B virus. Of the 233 subjects, 17 were positive for HBs-Ag (7%) implying current active hepatitis B infection of a chronic carrier state. The 213 dental practitioners were tested for anti-Hbs and 123 were found to be positive with an increasing percentage as the years of practice increase also. These data, backed up by statistical analysis, indicate that the prevalence of HBV among Philippine dental practitioners and clinicians is lee than 10% and that there is a direct relationship of this virus with the length of the year of dental practice which may be as a consequence of the constant risk of exposure to the virus through patients. When compared with 3 other countries, Philippine dentists were found to have the highest rate of Hepatitis B infectivity.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Hepatitis B; Occupational hazard